Factors affecting decision-making process in consumer purchasing behavior: case study Karamunsing Shopping Complex / Irene Samuel @ Liansim - Samuel @ Liansim, Irene (2012)
Consumer purchasing behaviour is important research topic in marketing sense due to fact that until there is a consumer there will be no business going on. Thus, to have a business is to have a marketing activity and practically the main centre of all this is consumer. Achieving business sustainability determine by marketing strategy in maximising profit. This study is aim to investigate the factors affecting consumer behaviour in their purchase decision-making process and to understand different characteristic of decision making styles. Respondents comprise of 85 males and females were evaluated on demographic. Research questionnaires designed by Sproles and Kendalls (1986) using Consumer Inventory Styles (CSI) were first test on data reliability using Cronbach Alpha Coefficients. Then Mann-Whitney test on gender and Kruskall-Wallis test for age, level of income and marital status to determine if there is significant factors influencing decision-making process among respondents. The finding indicates that there is no significant difference between male and female in term of decision-making process among respondents. Meanwhile there are significant difference in decision-making process among respondent based on age, income level and marital status. This study implies consumer decision-making process using CSI is applicable in local setting, as findings show similarities from previous research abroad and supports some part of the theory.